GESTIÓN ADMINISTRATIVA Y MARKETING ESTRATÉGICO EN UNA INSTITUCIÓN EDUCATIVA DE LIMA NORTE - ALVAREZ MORENO, Angela (2021)
This research has been carried out with the aim of establishing the Currently, public educational institutions do not require real Administrative Management of strategic educational Marketing towards students; since many times, they do not have a competitive vision compared to the services provided by private educational institutions. Therefore, the present investigation determined the significant relationship of Administrative Management and Strategic Marketing of an Institution of a basic Non-experimental design with the Correlational method. The population was 1,375 people among Directors, Administrators, Teachers, Parents and Students, of which they were selected as a non-probabilistic sample (385) under the Fisher, Arkin andColton procedure. An instrument was applied. For the hypothesis test, the SPSS 24 was applied, which yielded a positive relationship in favor of the general hypothesis, therefore it was concluded that Administrative Management is positively related to strategic Educational Marketing.